Editorial: Identifying Building Blocks of Sustainable Transport – Lessons on External Effects from Both Sides of the Atlantic - Perrels, Adriaan; Himanen, Veli; Lee-Gosselin, Martin (European Journal of Transport and Infrastructure Research, 2002)
Environmental and social impact assessment are default elements of transport policy preparation and transport project appraisal in many OECD countries. In the recent past however, it has been realised that such an approach does not suffice. Instead of representing possible limiting factors, the aims and principles of sustainable development are to be regarded as the very point of departure for formulating transport policies, as is for example formulated in the European Commission White Paper on Transport (COM, 2001). This has consequences not only for policy formulation, but also for theresearch that is used to build the evidence about the actual and potential impacts of transport systems.